Critical Success Factor in Monetizing Blog - Andika Rizky; Bens Pardamean (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Blog usage has transformed from its initial function as a digital diary into a legitimate form of mainstream media. Nowadays any member of the public can generate income from blogging through monetization even though various factors affect the results of this process. Four factors were identified: traffic, search engine optimization (SEO), post frequencies, and media usage. This study examines the level of importance of these factors through practical implementation into blogs then quantitatively determine which factor is critical for the success of blog monetization. An empirical analysis based on thirty samples of blogs were performed to assess the impact of the received income. The finding showed that the revenue for most of the blogs increased after the implementation of critical factors with SEO being the most critical of all the factors.